Rola społeczna mediów cyfrowych w orędziach papieża Franciszka z okazji Światowych Dni Środków Społecznego Przekazu - Koper, Damian (Pedagogika Społeczna Nova, 2024)
Pope Francis, in his messages on the occasion of the World Day of Social Communications, addresses currently important issues concerning communication in the digital world. Appreciating the achievements in the field of new media, he points to the need for media education. In this article, I have used the method of analyzing the content of eleven messages of Pope Francis in terms of the social role of digital media, subjecting them to synthesis and critical evaluation. The constant development of the media affects the relevance of the issue I am discussing. The Pope’s teaching expresses the position of the Church regarding the need for in-depth reflection on the proper understanding of the media’s tasks and role in shaping society.